Differential responses of size‐based functional groups to bottom–up and top–down perturbations in pelagic food webs: a meta‐analysis. Issue 11 (13th May 2014) - Hulot, Florence D.; Lacroix, Gérard; Loreau, Michel
<x xml:space="preserve">Abstract</x> We performed a meta‐analysis of 31 lake mesocosm experiments to investigate differences in the responses of pelagic food chains and food webs to nutrient enrichment and fish presence. Trophic levels were divided into size‐based functional groups (phytoplankton into highly edible and poorly edible algae, and zooplankton into small herbivores, large herbivores and omnivorous zooplankton) in the food webs. Our meta‐analysis shows that 1) nutrient enrichment has a positive effect on phytoplankton and zooplankton, while fish presence has a positive effect on phytoplankton and a negative effect on zooplankton in the food chains; 2) nutrient enrichment has a positive effect on highly edible algae and small herbivores, but no effect on poorly edible algae, large herbivores and omnivorous zooplankton in the food webs. Planktivorous fish have a positive effect on highly edible algae and small herbivores, a negative effect on large herbivores and omnivorous zooplankton, and no effect on poorly edible algae. Our meta‐analysis confirms that nutrient enrichment and planktivorous fish affect functional groups differentially within trophic levels, revealing important changes in the functioning of food webs. The analysis of fish effects shows the well‐described trophic cascade in the food chain and reveals two trophic cascades in the food web: one transmitted by large herbivores that benefit highly edible phytoplankton, and one transmitted by omnivorous zooplankton that benefit small herbivores. Comparison between the responses of food webs and simple food chains also shows consistent biomass compensation between functional groups within trophic levels.